2000
DOI: 10.1210/jcem.85.12.7167
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Strongly Stimulates Growth Hormone Release in Humans

Abstract: Ghrelin is a recently identified endogenous ligand for the GH secretagogue receptor and is involved in a novel system for regulating GH release. However, little is known about its GH-releasing activity and other endocrine effects in humans. To address this issue, we studied the GH, ACTH, cortisol, PRL, LH, FSH, and TSH responses to synthetic human ghrelin. In four normal male adults (28-37 yr), iv ghrelin administration released GH in a dose-dependent manner and 0.2, 1.0, and 5.0 microg/kg ghrelin produced 43.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
344
1
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 622 publications
(384 citation statements)
references
References 0 publications
12
344
1
19
Order By: Relevance
“…The GH-releasing activity of ghrelin is more marked in humans than in animals (Kojima et al, 1999;Seoane et al, 2000;Smith et al, 1997;Takaya et al, 2000). In humans, the GH response to ghrelin was considerably greater than that observed following administration of GHRH or synthetic GHSs (Arvat et al, 2001;Bowers, 2001;Seoane et al, 2000;Takaya et al, 2000), whereas in rats the GH-releasing potency of ghrelin was similar to that of GHRH (Kojima et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…The GH-releasing activity of ghrelin is more marked in humans than in animals (Kojima et al, 1999;Seoane et al, 2000;Smith et al, 1997;Takaya et al, 2000). In humans, the GH response to ghrelin was considerably greater than that observed following administration of GHRH or synthetic GHSs (Arvat et al, 2001;Bowers, 2001;Seoane et al, 2000;Takaya et al, 2000), whereas in rats the GH-releasing potency of ghrelin was similar to that of GHRH (Kojima et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Its structure is highly conserved among mammals, and it has been detected in chickens, fish and bullfrogs (Tritos and Kokkotou, 2006). Ghrelin is a potent secretogue of growth hormone from the pituitary through binding to the GHS receptor (Takaya et al, 2000). Circulating ghrelin exists in both an acylated and nonacylated form.…”
Section: Diverse Actions In Diverse Tissuesmentioning
confidence: 99%
“…Ghrelin, the endogenous ligand specific for the growth hormone (GH) secretagogue receptor, was discovered in 1999 by Kojima et al 1 Besides being a strong stimulator of GH secretion, 2,3 several studies have reported ghrelin to be a potent peptide involved in appetite and food regulation, as it increases food intake and promotes adiposity in both humans and animals. [4][5][6] Reduced levels have been reported in obese subjects, 7,8 whereas increased concentrations have been found in patients with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 99%